Sistem Pemantauan Rumah Kaca berbasis ESP32, Raspberry Pi, MQTT dan Node-RED - Christian Fredy Naa (Universitas Sam Ratulangi, 2022)
Greenhouse is a place to grow plants where the micro climate is controlled to achieve the best possible climate to grow plants. The micro climate involve three different states namely the state of the outside and inside air of the greenhouse and the state of the soil where the plants grow. The focus of this research is to design monitoring system which able to monitor those three states. The system is built based on four temperature and humidity sensors, two microcontoller ESP32, communication protocol MQTT and Node-RED. The sensors have been carefully selected in order to obtain particular measurements. The system has been tested for one day. The system is able to show the measurement data and record it in .csv format. The system is able to picture qualitatively the dynamics of weather and watering inside and outside of the greenhouse.